BIOMASSA SERASAH PADA BERBAGAI TIPE HUTAN ALAM DI NEGERI HATUSUA. PROVINSI MALUKU. - Abdul Latupono; Irwanto Irwanto; Miranda Hadijah (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Litter biomass is an essential component of forest ecosystems, playing a role in nutrient cycling, soil stability, and carbon storage. This study aims to measure and compare litter biomass across various types of natural forests in Hatusua Village, namely Coastal Forest, Mangrove Forest, Dominant Aren Forest, and Lowland Forest. The method used involved collecting litter samples from 2 × 2 meter plots, followed by drying and weighing to estimate dry biomass. The results showed that the highest litter biomass was found in Dominant Aren Forest (7,400.56 kg/ha), followed by Coastal Forest (5,773.71 kg/ha), Lowland Forest (1,798.55 kg/ha), and the lowest in Mangrove Forest (1,547.36 kg/ha). Differences in litter biomass among forest types were influenced by vegetation type, litter density, decomposition rates, and environmental conditions. This information is crucial for sustainable forest management and climate change mitigation through carbon storage in forest litter.